Mitigating the Menace of Boko Haram: The Media Conundrum - Ndinojuo, Ben-Collins Emeka (Faculty of Communications Science, Dr. Soetomo University, 2018)
Terrorism has become a recurrent feature in news headlines in both national and international news organisations. The Boko Haram group has become the foremost terrorist organisation in Nigeria and was labeled as the deadliest terrorist organisation by Global Terrorism Index of 2016 with over 6000 deaths to their name in 2015 alone. The United Nations recently released a report that over 5 million displaced persons by the Boko Haram conflict risk starvation and death in 2017. Their area of operation has expanded from Nigeria into Cameroon, Niger and Chad across sub-Saharan Africa and rumored to spread from Mali, Iraq and Syria with the pledge of allegiance by the Boko Haram Leader to the Islamic State (ISIS). This paper advocates that lack of viable community media organisations that provide information on rural communities may have played a part in the rise of the group. Journalists reporting conflicts are put in a complex situation where their access to conflict zones has been limited thus impacting on the quality of their reporting. The military is enjoined to provide greater access and protection for journalists covering the conflict as accuracy and objectivity are key elements in reporting and resolution of crises.